Developing the ecological scientist mindset among underrepresented students in ecology fields. Issue 6 (28th June 2021) - Bowser, Gillian; Cid, Carmen R.
Abstract: How do students discover ecology? Answering this question is essential for diversifying the environmental workforce because scientific disciplines, such as ecology, are often not discovered until students enter academia and are exposed to different disciplinary options. Ecology, and many of the environmental sciences, have persistent and alarmingly low numbers of underrepresented minorities (URM; African American, Hispanic American, Native American, and Pacific Islanders), while other science and technology fields have shown progress in diversification. Why does such underrepresentation persist in environmental disciplines? Social factors such as sense of belonging, science identity, implicit biases, and stereotypes all have been explored and are known to influence the participation of URM students in science. The unique role of the field experience in environmental sciences as a "rite of passage" and "authentic" research experience is one important influence on how URM students experience ecology. Interventions using social elements such as belonging and sense of place are demonstrated ways to broaden participation particularly in environmental science fields, yet dramatic underrepresentation still persists. Here we review known factors affecting and enhancing the recruitment and retention of URMs in the sciences and focus on comprehensive strategies shown to be effective recruiting URM students into the environmental workforce.